First Report on the Chemical Composition, Antioxidant Capacity, and Preliminary Toxicity to Artemia salina L. of Croton campinarensis Secco, A. Rosário & PE Berry (Euphorbiaceae) Essential Oil, and In Silico Study - Leonardo Souza da Costa; Ângelo Antônio Barbosa de Moraes; Jorddy Neves Cruz; Suraj N. Mali; Lorena Queiroz Almeida; Lidiane Diniz do Nascimento; Oberdan Oliveira Ferreira; Everton Luiz Pompeu Varela; Sandro Percário; Mozaniel Santana de Oliveira; Eloisa Helena de Aguiar Andrade (MDPI AG, 2022)
Croton campinarensis Secco, A. Rosário & PE Berry is an aromatic species recently discovered in the Amazon region. This study first reports the chemical profile, antioxidant capacity, and preliminary toxicity to A. salina Leach of the essential oil (EO) of this species. The phytochemical profile of the essential oil was analyzed by gas chromatography (GC/MS) and (GC-FID). The antioxidant capacity of the EO was measured by its inhibition of ABTS•+ and DPPH• radicals. Molecular modeling was used to evaluate the mode of interaction of the major compounds with acetylcholinesterase (AChE). The results indicate that the EO yield was 0.24%, and germacrene D (26.95%), bicyclogermacrene (17.08%), (E)-caryophyllene (17.06%), and δ-elemene (7.59%) were the major compounds of the EO sample. The EO showed a TEAC of 0.55 ± 0.04 mM·L−1 for the reduction of the ABTS•+ radical and 1.88 ± 0.08 mM·L−1 for the reduction of the DPPH• radical. Regarding preliminary toxicity, the EO was classified as toxic in the bioassay with A. salina (LC50 = 20.84 ± 4.84 µg·mL−1). Through molecular docking, it was found that the majority of the EO components were able to interact with the binding pocket of AChE, a molecular target related to toxicity evaluated in A. salina models; the main interactions were van der Waals and π-alkyl interactions.